Development E-module Making Sauces Food Processing and Serving Subjects in Vocational High Schools - Yuslita Eka Nanda; Rina Setyaningsih; Ika Wahyu Kusuma Wati (Universitas Negeri Padang, 2026)
This research is motivated by the fact that the learning media used is still limited to modules, package books, and jobsheets in the form of prints that are at risk of being easily damaged, and students are less interested in these media. The purpose of this research is to develop e-module media for making sauce; determine the feasibility of e-module media for making sauce; and find out the response of students to the use of e-module media for making sauce. The type of research used is Research and Development (R&D) with a four-D (4D) development model. The subject of the study was 36 students of class XI Culinary at SMK Negeri 1 Sewon Bantul. The data analysis technique uses quantitative descriptive analysis. The results of the research obtained were to produce sauce making e-module media in the form of links that can be accessed via smartphones or laptops; the feasibility of sauce making e-module media was declared very feasible with a percentage of 91.9% by material experts and 96.7% media experts; students' response to the use of sauce making e-module media It was stated based on the results of a small-scale trial with 6 student respondents obtaining a percentage of 85% with the category of very understanding, and the results of a limited scale trial with 30 student respondents obtaining a percentage of 92.08% with the category of very understanding. This shows that the e-module media for making sauce in food processing and serving is suitable for use in the learning process.